Therapeutic Algorithm for Use of Melatonin in Patients With COVID-19 - Reiter, Russel J.; Abreu-Gonzalez, Pedro; Marik, Paul E.; Dominguez-Rodriguez, Alberto (Frontiers in Medicine, 2020)
The coronavirus, COVID-19, has infected hundreds of thousands and killed tens of thousands of individuals worldwide. This highly infectious condition continues to ravage the world population and has yet to reach it peak infective rate in some countries. Many conventional drugs including hydroxychloroquine/chloroquine, lipinovir, remdisvir, etc., have been repurposed as treatments for this often deadly disease, but there is no specifically-designed effective drug available; also, these drugs mentioned have significant side effects and their efficacy is unknown. New drugs and vaccines are being designed as COVID-19 treatment, but their development and testing will require months to years. Time is not a luxury that this crisis has. Thus, there is a serious unmet need for the identification of currently-available and safe molecules which can be used to slow or treat COVID-19 disease. Several molecules have been suggested for this purpose, the best known of which may be vitamin C. Here, we suggest melatonin be given consideration for prophylactic use or treatment alone or in combination with other drugs. Melatonin’s multiple actions as an anti-inflammatory, anti-oxidant and anti-viral (against other viruses) make it a reasonable choice for use. Melatonin is readily available, can be easily synthesized in large quantities, is inexpensive, has a very high safety profile and can be easily self-administered. Melatonin is endogenously-produced molecule in small amounts with its production diminishing with increased age. Under the current critical conditions, large doses of melatonin alone or in combination with currently-recommended drugs, e.g., hydroxychloroquine/chloroquine, to resist COVID-19 infection would seem judicious.